Paths to the city : regional migration in nineteenth-century france - Moch, Leslie Page (Sage Publications, 1983)
Paths to the City presents a study of migration from rural areas to the industrializing city of Nimes in the 19th century. With unusual technical skill, Moch is able to reconstruct the lives of migrants in their villages and in the cities. She is able to separate them into separate streams of migrations; trace the work, marriage, and child-bearing patterns of migrants back to their rural roots; and compare migrants with people who did not move. She is also able to augment the demographic patterns she outlines with portraits of what happened to real individual people.